2004
DOI: 10.1073/pnas.0303452101
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation from invisible flicker

Abstract: Human ability to resolve temporal variation, or flicker, in the luminance (brightness) or chromaticity (color) of an image declines with increasing frequency and is limited, within the central visual field, to a critical flicker frequency of Ϸ50 and 25 Hz, respectively. Much remains unknown about the neural filtering that underlies this frequency-dependent attenuation of flicker sensitivity, most notably the number of filtering stages involved and their neural loci. Here we use the process of flicker adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 23 publications
8
75
0
1
Order By: Relevance
“…For instance, it has been shown that adaptation by a grating with a spatial frequency too high to be resolved by the visual system can nevertheless reduce observers' sensitivity to a resolvable grating at the same orientation, relative to sensitivity at the orthogonal orientation (He and MacLeod, 2001). Similarly, stimuli with undetectable flicker frequencies can cause adaptation to flicker at detectable frequencies (Shady et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that adaptation by a grating with a spatial frequency too high to be resolved by the visual system can nevertheless reduce observers' sensitivity to a resolvable grating at the same orientation, relative to sensitivity at the orthogonal orientation (He and MacLeod, 2001). Similarly, stimuli with undetectable flicker frequencies can cause adaptation to flicker at detectable frequencies (Shady et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A previous psychophysics study showed that flicker adaptation occurs from invisible luminance and chromatic flicker (13), and a functional magnetic resonance imaging (fMRI) study from our group found that the human brain responds to invisible chromatic flicker as far as visual area V4 (14), indicating that the invisible pattern information from chromatic flicker could be processed in retinotopic visual areas. Therefore, such stimuli allow us to ask whether, in the absence of awareness and related high-level cortex, invisible conflicting gratings can induce rivalry competition in the early visual cortex.…”
mentioning
confidence: 99%
“…S1]. Because flicker within this frequency range is expected to be subliminal [the critical flicker fusion frequency is Ͻ50 Hz with luminance levels obtained on CRT monitors (18)(19)(20)], it is possible to test the AttentionGamma hypothesis psychophysically by examining whether subliminal flicker (that should evoke neural synchronization within this frequency band) triggers attentional orientation.…”
mentioning
confidence: 99%